COMPARISON MEASUREMENT AND CALCULATION OF BRAIN TUMOR IN MRI MODALITIES UTILISING SPIN-ECHO PULSE SEQUENCE T1-WEIGHTED CONTRAST AND DIGITAL IMAGE PROCESSING APPLICATIONS - Putri, Maizza Nadia; Kusworo Adi; M.Irwan Katili; Sidin Hariyanto; Dwi Rochmayanti (Faculty of Vocational Studies, Universitas Airlangga, 2022)
Background: Evaluation of brain tumor MRI image results performed by radiologists employing the linear measurement method has several weaknesses and is sensitive to subjectivity. Purpose: To compare the results of measurements and calculations of brain tumors utilizing the linear measurement method on the Siemens 1.5 Tesla MRI modality employing pulse sequence spin echo with T1 contrast weighting compared with the results of measurements and calculations of brain tumors utilizing the active contour segmentation method. Method: An experimental study was conducted on 32 MRI images. Result: The study's findings indicated that the linear measurement was more significant than the active contour segmentation method (p-value<0,05). The results were obtained by calculating the sensitivity and specificity values of the diagnostic test, which were calculated to be 87.5%. Conclusion: The active contour segmentation method applied to pulse sequence spin-echo T1-weighted contrast can be utilized as an alternative measurement and calculation of brain tumors with a sensitivity and specificity value of 87.5%. Further research suggests developing a Matlab application to compare the results of measurements and calculations of brain tumors on acquiring 3D image magnetic resonance imaging data.